MODEL PEMBELAJARAN SNOWBALL THROWING UNTUK MENINGKATKAN KEAKTIFAN BELAJAR SISWA MATA PELAJARAN FIQIH - Mishbakhul Munir; Amir Gufron (Prodi Pendidikan Agama Islam, IAIN Sultan Amai Gorontalo, 2025)
Student activity is one of the important aspects in supporting the achievement of learning objectives. However, based on the results of field observations, it shows that student learning motivation in fiqh lessons is low. There needs to be a change in the learning model that can increase student activity in learning. The purpose of this study was to analyze the effect of the Snowball Throwing method in increasing student activity, especially in fiqh learning. The type of research used was a quasi-experimental study with a posttest-only control group design. The research sample used was 46 students divided into 2 classes, 25 students in the experimental class and 21 students in the control class. The sampling technique used random sampling. Data collection techniques were carried out using questionnaires and observation sheets to measure student activity. The data analysis used was descriptive analysis to analyze student activity. The results of the study showed that the level of student activity at MA Matholiul Huda who studied using the Snowball Throwing model was higher than students who studied with conventional learning models.